Penerapan Metode Belajar Aktif untuk Meningkatkan Partisipasi Anak dalam Pembelajaran Pendidikan Anak Usia Dini di TK Madiun (Eduscotech, 2022)
This study aims to determine the effect of applying active learning methods on increasing children's participation in Early Childhood Education (PAUD) at Madiun Kindergarten. Active learning methods are believed to encourage students' direct involvement in the learning process, increase their self-confidence, and create a pleasant learning atmosphere. This study employs a quantitative approach with an experimental research design, involving two groups: an experimental group where the active learning method is applied and a control group using conventional methods. Data collection was conducted through observations of children's participation during learning activities and interviews with early childhood education teachers. The research results showed that the implementation of active learning methods successfully increased children's participation significantly, both in verbal and non-verbal aspects. Overall, children who participated in learning using the active method showed higher enthusiasm, were more willing to ask questions, and were more active in learning activities. This study suggests that TK Madiun should further optimize the application of active learning methods in every learning session to support children's development at an early age.